EKSISTENSI ADVOKAT DALAM PEMBELAAN TERDAKWA PADA DUGAAN PENYALAHGUNAAN KEWENANGAN DI PENGADILAN TINDAK PIDANA KORUPSI PADA PENGADILAN NEGERI PEKANBARU - Tigo, Kevin; Diana, Ledy; ', Erdianto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
In the process of criminal justice, defense lawyers typically do with providing legal assistance to the accused in defending and protecting the interests of fundamental rights of freedom of justice seekers. advocates not just accompany the accused in the trial, but with all his knowledge to defend, prove the accused not guilty and uphold the interests of the defendant, both in substance law and legal procedure. Law Number 30 Year 2014 About the Administration, stating the elements of abuse of authority as stipulated in the law on Corruption Eradication must be assessed by the State Administrative Court. Here it takes the role and existence of the Advocate in defending the interests of the defendant to actively and intelligently in exploring and understanding the legislation, to ensure legal certainty on the defendant himself.As for the purpose of this thesis is how the existence of an advocate in defense of the accused in the alleged Misuse of Authority in the Corruption Court In Pekanbaru District Court and what are the obstacles encountered in the defense of the accused in the alleged abuse of authorityFrom the research problem can be concluded, first, the existence of an advocate in defense of the accused in the trial, has significant value for accused persons to prove whether he is guilty or not guilty. In the case of allegations of abuse of authority, Advocate provides legal assistance to the accused optimally including by ensuring the implementation of the testing element has been abuse of authority by the State Administrative Court before the alleged abuse of authority inspected or tried at the Corruption Court. The second, in stints profession Advocate gets constraints, namely: lack of legal awareness of the accused, not pahamnya advocate in legal developments, the stigma society has opined defendant guilty before the court decides, the difficulty of presenting defense witnesses / prove the defendant not guilty, and their menyelesaian judicial mafia is no longer a case based on facts so professional, quality, and ability to advocate no longer needed.Keywords: Advocate - Abuse of Power - Corruption Court